Employee loyalty evaluation using machine learning in technology-based small and medium-sized enterprises - Yong Shi; Yuan Wang; Hongkun zuo (Scientific Reports)
Abstract Employee loyalty is a major issue of sustainable human resource management. Small and medium-sized enterprises with high technology content and strong innovation ability are the main body of innovation with great vitality and potential. Employee loyalty is an important factor for the success and development of Technology-based Small and Medium-sized Enterprises (TSMEs). This research starts with the historical evaluation data of employees in Chinese TSMEs to analyze the relevant factors of employee loyalty and the relationship between these factors and employee loyalty. Through several machine learning models and algorithms to predict employee loyalty, the feasibility of machine learning to predict employee loyalty is proved, and the evaluation of talent in TSMEs is supported by decision analysis. This research aims to build an objective and applicable intelligent evaluation model of employee loyalty to support TSMEs to accurately identify, motivate, attract, cultivate and retain outstanding scientific and technological talents. This study contributes to the promotion of sustainable and high-quality management of TSMEs.